The Posture of Words - Rambo, Shelly (Literature and theology, 2019)
Growing research in trauma focuses on working trauma out of the body. This somatic turn' can minimise the role that narrative plays in healing. This piece imagines a coordination between writing, words, and the senses that is in line with the wisdom of longstanding religious traditions. It proposes that theopoetics positions us to release the negative grip of words while creating, through words, new paths of meaning.